Analisis Ketepatan Waktu Pengiriman Terhadap Kepuasan Konsumen pada J&T Express Kota Bima - Supriyadin Supriyadin; Amirulmukminin Amirulmukminin; Nurhayati Nurhayati (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2024)
To determine satisfaction when using expedition services, timeliness is the main reason in determining consumer satisfaction when using a service. The aim of this research is to determine the effect of timeliness of delivery on consumer satisfaction at J&T Express Bima City. The type of research is associative. The research instrument uses questionnaire with a Likert scale. The population used in this research is all consumers who have used J&T Express services, the number of which is unknown (Unknown Population). The number of samples used in this research was 96 respondents with a sampling technique, namely purposive sampling. Data collection techniques using observation, questionnaires and literature study. Data analysis techniques by carrying out validity tests, reliability tests, simple linear regression tests, correlation coefficients, determination tests, and t tests. The results of this research show that on time delivery has a significant effect on consumer satisfaction at J&T Express, Bima City.